Risk factors for lymphoedema in women with breast cancer: A large prospective cohort. (August 2016) - Kilbreath, S.L.; Refshauge, K.M.; Beith, J.M.; Ward, L.C.; Ung, O.A.; Dylke, E.S.; French, J.R.; Yee, J.; Koelmeyer, L.; Gaitatzis, K.
Abstract: A prospective study was conducted to identify women at increased risk for lymphoedema (LE) based on axillary surgery. Assessment occurred prior to surgery, within 4 weeks, and at 6, 12 and 18 months following surgery. Following post-surgery assessment, women were asked to complete weekly diaries regarding events that occurred in the previous week. Risk factors were grouped into demographic, lifestyle, breast cancer treatment-related, arm swelling-related, and post-surgical activities. Bioimpedance spectroscopy thresholds were used to determine presence of LE. At 18-months, 241 women with <5 nodes removed and 209 women with ≥5 nodes removed were assessed. For those with <5 nodes removed, LE was present in 3.3% compared with 18.2% for those with ≥5 nodes removed. There were insufficient events to identify risk factors for those with <5 nodes removed; for those with >5 nodes removed, independent risk factors included presence of arm swelling at 12-months (Odds Ratio (OR): 13.5, 95% CI 4.8, 38.1; P < 0.01), at 6-months (5.6 (2.0, 16.9); P < 0.01), and radiotherapy to the axilla (2.6 (0.7, 8.9); P = 0.14). Arm swelling at 6 and 12 months was associated with taxane-based chemotherapy, high body weight at diagnosis and arm swelling within 4 weeks post-surgery. Of the post-surgical events assessed in a sub-group of women with >5 nodes removed and who maintained weekly diaries, only blood drawn from the 'at-risk' arm was identified as a potential risk (OR 2.0; 0.8, 5.2). For women with ≥5 nodes removed, arm swelling in the first year poses a very strong risk for presence of LE at 18-months. Highlights: Risk factors for lymphoedema (LE) differ dependent on number of nodes removed. Strongest risk of LE at 18 m was swelling in the first 12 m when ≥5 nodes removed. LE in the first 12 m is associated with taxanes and overweight when ≥5 nodes removed. Factors for which women are typically cautioned were not identified as a risk for LE.